Investigation of biologically active substances of the North Caucasus plant raw materials using various preservation methods - N. O. Sichko; M. I. Stalnaya (Новые технологии)
Introduction. When storing medicinal plant material, in order to ensure the preservation of the maximum number of biologically active components, it is necessary to slow down the biochemical processes by preservation. Today, studies on changes in the physicochemical composition of biologically active substances (BAS) of plant raw materials, including fruits and leaves, are relevant in order to establish the optimal method that allows preserving the main qualities of the raw materials. In order to increase the production volumes of local domestic medicinal herbal preparations, freezing and drying should be introduced along with the traditional freshly picked use of medicinal plants.The goal of the research was to study biologically active substances of fresh, frozen and dried basil leaves of three varieties growing in the North Caucasus.The methods. Standard methods of analysis of plant materials were used in the research.The results. It has been found that the freezing process is widely used in the preservation of food plant materials, but it is not used in pharmaceutical practice. This is due to the scarce information on the chemical composition of biologically active substances of most types of frozen medicinal plant materials, as well as comparative studies on the content of biologically active substances in fresh, dried and frozen raw materials. The article presents original information on the study of the chemical composition and biologically active compounds of fresh, frozen and dried basil greens of three varieties (Velvet, Ararat, Gvozdichny) growing in the North Caucasus. It is shown that extracts from the aboveground organs of basil have pronounced antioxidant activity. Depending on the preservation method used, the following biologically important compounds have been identified in the quantitative study: chlorophyll, carotenoids, ascorbic acid, and the antioxidant activity of the raw materials has also been established.The Conclusion. The results obtained prove the prospects of the conducted scientific research, which has not only theoretical but also practical significance for the purpose of creating new products using fresh, frozen and dried basil greens with a high content of natural antioxidants (biologically active substances) and creating functional drinks.